Cell: A molecular approach - Cooper, Geoffrey M.; Cooper, Geoffrey M.; Hausman, Robert E. (Sunderland, Sinauer, 2016)
Because molecular and cellular biology is such an exciting and rapidly moving area of science, teaching it at the undergraduate level is a rewarding, yet challenging, task. The A Molecular Approach meets this challenge by providing students with not only the most current information, but also with an introduction to the experimental nature of contemporary research. Designed for use in introductory cell biology courses, The Cell presents current comprehensive science in a readable and cohesive text that students can master in the course of one semester. The new Third Edition of The Cell retains the organization, themes, and special features of earlier editions, but is updated to reflect scientific advances since publication of the Second Edition in 2000, * progress that has been made in genome sequencing * advances in understanding transcriptional regulation and mRNA processing * the use of DNA microarrays in global studies of gene expression and cancer diagnostics * advances in nuclear transport and protein trafficking * progress in understanding the regulation of programmed cell death * potential medical applications of embryonic stem cells * the development of oncogene-targeted cancer treatmentsSPECIAL FEATURES OF THE CELLWith a clear focus on cell biology as an integrative theme, topics such as developmental biology, plant biology, the immune system, the nervous system, and muscle physiology are covered in their broader biological context."Key Experiment" boxes in each chapter describe seminal experiments in modern cell biology, showing the details and background to give students a sense of doing science."Molecular Medicine" boxes relate basic science to clinical practice or potential and show the excitement of molecular discovery and solutions to disease.Chapter summaries are organized in outline form corresponding to the major sections and subsections of each chapter. This section-by-section format is coupled with a list of the key terms introduced in each section, providing a succinct but comprehensive review of the material.The full-color art program is both pedagogically and scientifically outstanding.In addition, each chapter a brief chapter outline, bold-faced key terms (also defined in the glossary), and chapter-end questions (15 per chapter) with answers in the back of the book. The deliberate and cumulative result of this pedagogy is a book that students can master.
Glossary 783-802p.; Index 895-832p.
Keywords: Bionergetics and metabolism; Cell cycle; Cell signaling; Cancer